Molecular systematics of Ceratostomella sensu lato and morphologically similar fungi - Réblová, Martina (Mycologia, 2006)
The systematic position and phylogenetic relationships of Ceratostomella sensu lato and phenotypically similar fungi using comparative morphological and culture studies and phylogenetic analyses of the nuclear large- and small-subunit ribosomal DNA were explored. In the light of inferred phylogenies and morphological data the genus Ceratostomella is redescribed, the generic concept is emended and four species are accepted (viz. C. cuspidata, C. pyrenaica, C. rhynchophora and C. rostrata). A new genus Xylomelasma is introduced and delimited from Ceratostomella, with two new species described (viz. X. novaezelandiae and X. sordida). In culture species of both Ceratostomella and Xylomelasma produced sterile mycelium. The genus Lentomitella with a phaeoisaria-like anamorph formed in vitro is reinstated to encompass taxa formerly attributed to the broadly perceived Ceratostomella with three accepted species (viz. L. cirrhosa, L. crinigera and L. tomentosa). Lentomitella and Ceratostomella are clearly distinguishable by the morphology of asci, ascospores and centrum. Lentomitella is compared to phenotypically similar Ceratosphaeria, which formed a harpophora-like anamorph in vitro. In the present phylogenies Ceratostomella, Ceratosphaeria, Lentomitella and Xylomelasma are shown as clearly separate genera belonging to three different groups of perithecial ascomycetes. Ceratostomella, Lentomitella and Xylomelasma reside within a large unsupported clade consisting of members the Ophiostomatales, the freshwater Annulatascaceae and a group of nonstromatic, terrestrial taxa. Ceratosphaeria is well supported within the Magnaporthaceae. The systematic value of morphological characters of ascospores, paraphyses, asci, centrum and conidiogenesis in segregating taxa from Ceratostomella sensu lato and their relatives is discussed.
Keywords: mycelium; DNA, Fungal; fylogeneze; Photomicrography; Sequence Analysis, DNA; Phylogeny; ribozomální DNA; sekvenční analýza DNA; molekulární sekvence - údaje; Microscopy; Spores, Fungal; DNA fungální; geny rRNA; spory hub; Genes, rRNA; mikroskopie; Ascomycota; Mycelium; Molecular Sequence Data; DNA, Ribosomal; mikrofotografie